2022
DOI: 10.3389/fimmu.2022.1050917
|View full text |Cite
|
Sign up to set email alerts
|

Research progress on anti-ovarian cancer mechanism of miRNA regulating tumor microenvironment

Abstract: Ovarian cancer is the most deadly malignancy among women, but its complex pathogenesis is unknown. Most patients with ovarian cancer have a poor prognosis due to high recurrence rates and chemotherapy resistance as well as the lack of effective early diagnostic methods. The tumor microenvironment mainly includes extracellular matrix, CAFs, tumor angiogenesis and immune-associated cells. The interaction between tumor cells and TME plays a key role in tumorigenesis, progression, metastasis and treatment, affecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 130 publications
0
3
0
Order By: Relevance
“…Serum-based biomarkers are considered the optimal Recent studies underscore the importance of placing greater emphasis on exosomal MicroRNA (miRNA), which is extensively implicated in the development of the epithelial ovarian cancer tumor microenvironment (EOC-TME). This emphasizes its crucial role in both the initiation and progression of tumors [30,31]. Several researchers have examined the expression profiles of miRNAs in serum samples from individuals with EOC, with the goal of identifying biomarkers for the condition [30,32].…”
Section: Serum-based Eoc Biomarkersmentioning
confidence: 99%
See 1 more Smart Citation
“…Serum-based biomarkers are considered the optimal Recent studies underscore the importance of placing greater emphasis on exosomal MicroRNA (miRNA), which is extensively implicated in the development of the epithelial ovarian cancer tumor microenvironment (EOC-TME). This emphasizes its crucial role in both the initiation and progression of tumors [30,31]. Several researchers have examined the expression profiles of miRNAs in serum samples from individuals with EOC, with the goal of identifying biomarkers for the condition [30,32].…”
Section: Serum-based Eoc Biomarkersmentioning
confidence: 99%
“…This emphasizes its crucial role in both the initiation and progression of tumors [30,31]. Several researchers have examined the expression profiles of miRNAs in serum samples from individuals with EOC, with the goal of identifying biomarkers for the condition [30,32]. Although a specific study effectively identified certain circulating miRNAs consistently linked to epithelial ovarian cancer (EOC), there is a lack of consensus regarding the methodologies employed [32], and the costs associated with miRNA profiling are substantial [24].…”
Section: Serum-based Eoc Biomarkersmentioning
confidence: 99%
“…miRNA is a type of endogenous small noncoding RNA (sncRNA) comprising 18 25 nucleotides that regulates physiological functions including cellular growth, proliferation, and apoptosis ( 16 , 17 ). Several reports have revealed the significant involvement of miRNAs in various malignant processes of OC oncogenesis ( 18 , 19 ). In human malignancies, cross-modulation between miRNAs and lncRNAs has recently been found in multiple studies.…”
Section: Introductionmentioning
confidence: 99%